Pertumbuhan Tiga Varietas Cabai Merah (Capsicum annuumL.) Terpapar Cekaman Muka Air Tanah Dangkal di Awal Fase Vegetatif - Erna Siaga; Mei Meihana; Friscka Harifitri Utami; Santa Maria Lumbantoruan (Politeknik Negeri Lampung., 2024)
Red chili (Capsicum annuum L.) is a featured commodity for horticultural crops which has high economic value and potential to developed in Indonesia. One of the developments which need to be carried out is chili peppers cultivation on riparian tropical wetland during transition period (drought-flood).The aim of this study was to evaluate the growth response of three varieties of red chili to water stress conditions, namely shallow water table (SWT) at vegetative phase. This study used completely randomized design with chili pepper varieties treatment which consisting of Laris (V1), Laba F1 (V2), and Laju F1 (V3) during seven days of SWT and seven days of recovery. The results showed that SWT conditions had an effect in the form of an increase in the shoot length, root length and number of leaves of chili plants, and decreased after recovery conditions, except for root length, while the three varieties used in the study did not show significantly affected by SWT. In the results of agronomic characters, namely shoot dry weight, root dry weight, and total dry weight, there was also an increase in the three varieties of chili plants, both after SWT treatment and after recovery. The highest adaptability to shallow water table conditions in order are the varieties Laju F1, Laga F1 and Laris. Red chili pepper plants is categorized as resistant horticultural commodity on shallow water table stress conditions at vegetative phase and potential to be cultivated at riparian tropical wetland during transition period.